A designable aminophenylboronic acid functionalized magnetic Fe3O4/ZIF-8/APBA for specific recognition of glycoproteins and glycopeptides. Issue 13 (12th February 2018) - Li, Shanshan; Li, Dongyan; Sun, Long; Yao, Yuewei; Yao, Cheng
Abstract : We fabricated a novel aminophenylboronic acid functionalized magnetic Fe3 O4 /zeolitic imidazolate framework-8/APBA (denoted as Fe3 O4 /ZIF-8/APBA). Abstract : We fabricated a novel aminophenylboronic acid functionalized magnetic Fe3 O4 /zeolitic imidazolate framework-8/APBA (denoted as Fe3 O4 /ZIF-8/APBA). First, Fe3 O4 was coated by zeolitic imidazolate framework-8 (denoted as Fe3 O4 /ZIF-8) using the hydrothermal method. Next, the phenylboronic acid functionalized triethoxysilane reagent was synthesized by 3-aminophenylboronic acid and 3-isocyanatopropyltriethoxysilane, which was modified on the surface of the Fe3 O4 /ZIF-8 nanocomposite through the sol–gel technique and electrostatic interaction as well as π–π stacking interaction. The synthetic Fe3 O4 /ZIF-8/APBA exhibited high adsorption capacity and good specificity toward glycoproteins. Moreover, the Fe3 O4 /ZIF-8/APBA possessed high saturation magnetization (51.41 emu g −1 ) and achieved better separation in the presence of an external magnetic field. Above all, the as-designed Fe3 O4 /ZIF-8/APBA was successfully used to capture glycoproteins and identify the horseradish peroxidase (HRP) tryptic digest. This study provides a facile strategy to embellish the aminophenylboronic acid onto the nanocomposite substrate and develop a new material for the specific recognition and enrichment of glycoproteins and low-abundance glycopeptides in proteomics research.